Analysis of sociocultural identities, country images and psychic distance in international study destination choice - Hendriana, Evelyn (2019)
Intense competition in international higher education industry invokes the need to study on factors leading up to students’ choice of study destination. These influencing factors may be different between students who choose studying in traditional and new educational destinations. Since students’ decision to study abroad is a complex process, it would be necessary to have comprehensive understanding about this process by looking at the cognitive and psychological factors. This study aims to explain the phenomenon in international higher education industry through the lens of international marketing by integrating the cognitive, affective, and normative elements of foreign purchasing behavior. The main objective of the study is to examine the influence of sociocultural identities, country images, and psychic distance on students’ choice of study destination using destination and institution images as mediating variables. This study also explores the potential moderating role of country images and psychic distance in the relationship between sociocultural identities, destination and institution images. The relationships between variables of interest are explained by social identity theory, attitude theory, and similarity-attraction theory. This study applied a quantitative research approach to test ten hypotheses. Samples of senior high school students in eight provinces in Indonesia were selected using multistage cluster sampling technique. In total, 888 responses were analyzed using structural equation modeling. This study found that destination and institution images mediated the relationship between sociocultural identities, country images, psychic distance, and students’ intention to study in foreign destination. There was a slight difference on the factors influencing students' intention to study in Australia and Malaysia. Students’ intention to study in Australia was influenced by consumer cosmopolitanism, country images, and psychic distance, whereas intention to study in Malaysia was affected by consumer cosmopolitanism and country images. The proposed hypotheses on the moderating role of country images and psychic distance in the relationship between sociocultural identities, destination and institution images were partially supported. The findings suggest that marketers of international education and the government of host country must align their strategy to create a distinct and outstanding cognitive country image, as well as evoke positive emotions toward the host country, to attract Indonesian students.